Conan the barbarian (2011) [videorecording (DVD)] - Nispel, Marcus, 1964-; Momoa, Jason; Nichols, Rachel, 1980-; Perlman, Ron, 1950-; Lang, Stephen, 1952-; McGowan, Rose, 1973-; Taghmaoui, Saïd (Lionsgate, 2011)
"A quest that begins as a personal vendetta for the fierce Cimmerian warrior soon turns into an epic battle against hulking rivals, horrific monsters, and impossible odds, as Conan realizes he is the only hope of saving the great nations of Hyboria from an encroaching reign of supernatural evil"--Container.